Cholera outbreaks in Nigeria are associated with multidrug resistant atypical El Tor and non-O1/non-O139 Vibrio cholerae. - Michel A Marin; Cristiane C Thompson; Fernanda S Freitas; Erica L Fonseca; A Oladipo Aboderin; Sambo B Zailani; Naa Kwarley E Quartey; Iruka N Okeke; Ana Carolina P Vicente (Public Library of Science (PLoS), 2013)
BACKGROUND: The current millennium has seen a steep rise in the number, size and case-fatalities of cholera outbreaks in many African countries. Over 40,000 cases of cholera were reported from Nigeria in 2010. Variants of Vibrio cholerae O1 El Tor biotype have emerged but very little is known about strains causing cholera outbreaks in West Africa, which is crucial for the implementation of interventions to control epidemic cholera. METHODOLOGY/PRINCIPAL FINDINGS: V. cholerae isolates from outbreaks of acute watery diarrhea in Nigeria from December, 2009 to October, 2010 were identified by standard culture methods. Fifteen O1 and five non-O1/non-O139 strains were analyzed; PCR and sequencing targeted regions associated with virulence, resistance and biotype were performed. We also studied genetic interrelatedness among the strains by multilocus sequence analysis and pulsed-field gel electrophoresis. The antibiotic susceptibility was tested by the disk diffusion method and E-test. We found that multidrug resistant atypical El Tor strains, with reduced susceptibility to ciprofloxacin and chloramphenicol, characterized by the presence of the SXT element, and gyrA(Ser83Ile)/parC(Ser85Leu) alleles as well CTX phage and TCP cluster characterized by rstR(ElTor), ctxB-7 and tcpA(CIRS) alleles, respectively, were largely responsible for cholera outbreaks in 2009 and 2010. We also identified and characterized a V. cholerae non-O1/non-O139 lineage from cholera-like diarrhea cases in Nigeria. CONCLUSIONS/SIGNIFICANCE: The recent Nigeria outbreaks have been determined by multidrug resistant atypical El Tor and non-O1/non-O139 V. cholerae strains, and it seems that the typical El Tor, from the beginning of seventh cholera pandemic, is no longer epidemic/endemic in this country. This scenario is similar to the East Africa, Asia and Caribbean countries. The detection of a highly virulent, antimicrobial resistant lineage in Nigeria is worrisome and points to a need for vaccine-based control of the disease. This study has also revealed the putative importance of non-O1/non-O139 V. cholerae in diarrheal disease in Nigeria.